Improved tropical forest management for carbon retention - Putz, F.E.; Zuidema, Pieter A.; Pinard, M.A.; Boot, R.G.A.; Sayer, Jeffrey A.; Sheil, Douglas; Sist, P.; Vanclay, J.K. (Public Library of Science, 2008)
Using reduced-impact timber-harvesting practices in legally logged tropical forests would reduce global carbon emissions by 0.16 Gt/year at a modest cost and with little risk of "leakage" (increased carbon emissions elsewhere).